IMPLEMENTASI SISTEM INFORMASI KEARSIPAN DINAMIS TERINTEGRASI (SRIKANDI) DI DINAS KEARSIPAN DAN PERPUSTAKAAN KOTA KUPANG - Ladapase, Yosefa Freinademetz Aso; Niga, Jacoba D.; Long, Belandina L.; Pandie, Ardy Y. (Journal Education and Government Wiyata, 2025)
This study aims to determine the implementation of the Integrated Dynamic Archival Information System (SRIKANDI) at the Kupang City Archives and Library Office. Using descriptive qualitative method, this research describes phenomena systematically, factually, and accurately based on data obtained from interviews, observations, and document studies. This research refers to Edward III's theory which includes four aspects: communication, resources, disposition, and bureaucratic structure. The research informants consisted of 8 people, including the Head of Office, Head of Division, Expert Archivist, and employees of the Archives and Library Office. The results showed that the implementation of SRIKANDI has been effective in terms of communication, with socialisation and technical guidance carried out although there are still employees who have not used the application. Existing resources, both human, budget, and facilities, support the implementation of SRIKANDI, although there are internet network constraints that need to be improved. Employees' disposition towards the application is positive, as the application facilitates the correspondence process and saves time and money. In addition, the Kupang City Archives and Library Office has followed the Standard Operating Procedures (SOP) set by the National Archives of the Republic of Indonesia (ANRI) well and systematically.